Effects of Dip-Coating Processing Parameters on the Functional Performances of Ti$_3$C$_2$T$_x$ MXene-Silk Yarns (Journal of Fiber Bioengineering and Informatics, 2023)
Mxenes, as a new group of two-dimensional materials in form of transition metal carbides, carbonitridesand/or nitrides, have been playing an important role in the wearable smart electronic field. Due to theirabundance surface functional groups, Mxenes have showed their superior dispersions in various solventswhich is beneficial to simply the fabrication process of textile-based electronics while their electricalperformance guaranteed. In this work, we report a novel fine silk yarn dip-coated in an aqueous solution of ${\rm Ti}_3{\rm C}_2{\rm T}_x$ MXene to obtain low electrical resistance (∼25.6 Ohms/cm). Yarns structures and morphologieswere observed by transmission and scanning electron microscopy (TEM & SEM) together with energydispersive spectroscopy (EDS). Besides, Fourier transform infrared (FTIR) and Raman spectroscopy, andX-ray diffraction (XRD) analysis were carried out to reveal the chemical compositions. By controllingtwo coating parameters as design of experiments (DoE) factors, we found both solution concentrationand soaking time had significant effects on yarn performances. The mechanical performance of yarnfabricated under the optimised coating condition was evaluated by means of tensile testing, resulting ina significant 23% increase in breaking strength (∼107 MPa). In responding to tensile deformation, thedip-coated yarn also performed a linear variation in resistance, which indicated its capability in sensingapplications.
Keywords: MXenes; Electrically Conductive Yarns; Dip-coating; DoE; Yarn Tensile Strength